Exploring vascular contributions to cognitive impairment and dementia (ENIGMA): protocol for a prospective observational study - Sigrid Breinholt Vestergaard; Andreas Gammelgaard Damsbo; Niels Lech Pedersen; Katrine Zachariassen; Kim Ryun Drasbek; Leif Østergaard; Grethe Andersen; Rikke Beese Dalby; Janne Kærgård Mortensen (BMC Neurology, 2024)
Abstract Background Post-stroke cognitive impairment (PSCI) is common. However, the underlying pathophysiology remains largely unknown. Understanding the role of microvascular changes and finding markers that can predict PSCI, could be a first step towards better screening and management of PSCI. Capillary dysfunction is a pathological feature of cerebral small vessel disease and may play a role in the mechanisms underlying PSCI. Extracellular vesicles (EVs) are secreted from cells and may act as disease biomarkers. We aim to investigate the role of capillary dysfunction in PSCI and the associations between EV characteristics and cognitive function one year after acute ischemic stroke (AIS) and transient ischemic attack (TIA). Methods The ENIGMA study is a single-centre prospective clinical observational study conducted at Aarhus University Hospital, Denmark. Consecutive patients with AIS and TIA are included and followed for one year with follow-up visits at three and 12 months. An MRI is performed at 24 h and 12 months follow-up. EV characteristics will be characterised from blood samples drawn at 24 h and three months follow-up. Cognitive function is assessed three and 12 months after AIS and TIA using the Repeatable Battery for the Assessment of Neuropsychological Status. Discussion Using novel imaging and molecular biological techniques the ENIGMA study will provide new knowledge about the vascular contributions to cognitive decline and dementia. Trial registration The study is retrospectively registered as an ongoing observational study at ClinicalTrials.gov with the identifier NCT06257823.